ANALISA DETEKSI GELOMBANG QRS UNTUK MENENTUKAN KELAINAN FUNGSI KERJA JANTUNG - Evrita Lusiana Utari (Teknoin, 2016)
Mortality rate by heart disease in Indonesia is up to 26%. To prevent the higher of mortality rate by heart disease, an early examination for heart can be done by taking the record of electrocardiograph. The record was analyzed to know the heart rhythm that can be indication of heart disorder. By applying the warning of heart disorder, the heart condition and the treatment can be known rapidly. Electrocardiography record can be done in a short time, i.e. for 5 minutes (short term). Analyzing method in the time domain is the simplest way to analyze the variation of the heart rate. Analyzing in the time domain for R interval and the heart rate can be done by histogram and statistical analysis. Measurement method in the time domain is divided into two parts statistically, i.e. directly measurement for normal condition in R interval or the heart rate include the average value, and the standard deviation. The wavelet method was used in the QRS detection method in this research. Wavelet was designed to signal data processing, data filtering, thresholding, and histogram, to acquire the average of QRS wave, and its deviation standard. The benefit of the wavelet method can obtained the negative deflection value for Q wave with the amplitude 25% of R wave, R wave obtained positive deflection with the amplitude 1,6 – 3 mV, and negative deflection for S wave has the amplitude between 0,1 mV up to 0,5 mV.